The Effect of Washing Methods on The Quality of Etawah Goat Sperm - H.Y. Lukman; I Wayan Lanus Sumadiasa; Enny Yuliani; Lalu Ahmad Zaenuri; Aminurrahman; Musanip (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
This study aims to evaluate the effectiveness of washing methods (swim-up and centrifugation) in an isotonic medium on the quality of Crossbred Etawah (PE) goat sperm. The material used was fresh semen from healthy male PE goats aged 2-3 years. Sperm collection was carried out using an artificial vagina twice a week. Immediately after semen collection, the quality of fresh semen was examined macroscopically and microscopically. Based on the results of this examination, it was declared good and then processed for research. The research method used in this study was a laboratory experiment using a Completely Randomized Design (CRD) with three treatments and seven replicates. The semen was divided into three parts as treatments. P0 was the control without washing. The isotonic solution with andromed medium was treated with P1, which was centrifuged at 1500 rpm for 15 minutes, and P2 (sperm swimming in isotonic solution with andromed medium). The variables observed were progressive motility, viability, intact plasma membrane (IPM), and spermatozoa abnormalities. The data were analysed using analysis of variance (ANOVA) and Duncan's post hoc test in SPSS 16. The results showed that the best percentage of motility, viability, intact plasma membrane, and spermatozoa abnormalities in 7-hour storage at room temperature were in P0 at 54.00±8.21, 57.20±8.98, 52.00±7.58, and sperm abnormalities at P1 were slightly better at 5.00±3.31. The analysis between treatments P0 and P1 did not show a significant difference, but treatment P2 showed a significant difference. Contribution to Sustainable Development Goals (SDGs):SDG 2 : No HungerSDG 3 : Good Health and Well-BeingSDG 4 : Quality EducationSDG 12: Responsible Consumption and Production